Activity Energy Expenditure and Mobility Limitation in Older Adults: Differential Associations by Sex - Manini, Todd M. (Oxford University Press, 2009)
In this study, the authors aimed to determine whether higher activity energy expenditure, assessed by using doubly labeled water, was associated with a reduced decline in mobility limitation among 248 older community-dwelling US adults aged 70–82 years enrolled in 1998–1999. Activity energy expenditure was calculated as total energy expenditure (assessed over 2 weeks by using doubly labeled water) minus resting metabolic rate (measured with indirect calorimetry), with adjustment for the thermic effect of food. Across sex-specific tertiles of activity energy expenditure, men in the lowest activity group experienced twice the rate of mobility limitation as men in the highest activity group (41% (n = 18) vs. 18% (n = 8)). Conversely, women in the lowest and highest activity groups exhibited similarly high rates of mobility limitation (40% (n = 16) vs. 38% (n = 15)). After adjustment for potential confounders, men with higher activity energy expenditure levels continued to show reduced risk of mobility limitation (per standard deviation (284 kcal/day): hazard ratio = 0.61, 95% confidence interval: 0.41, 0.92). Women showed no association (per standard deviation (226 kcal/day): hazard ratio = 1.34, 95% confidence interval: 0.98, 1.85). Greater energy expenditure from any and all physical activity was significantly associated with reduced risk of developing mobility limitation among men, but not among women.